2010
DOI: 10.2527/jas.2009-2311
|View full text |Cite
|
Sign up to set email alerts
|

Fetal programming of skeletal muscle development in ruminant animals1

Abstract: Enhancing skeletal muscle growth is crucial for animal agriculture because skeletal muscle provides meat for human consumption. An increasing body of evidence shows that the level of maternal nutrition alters fetal skeletal muscle development, with long-term effects on offspring growth and performance. Fetal skeletal muscle development mainly involves myogenesis (i.e., muscle cell development), but also involves adipogenesis (i.e., adipocyte development) and fibrogenesis (i.e., fibroblast development). These t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
422
2
34

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 423 publications
(469 citation statements)
references
References 87 publications
11
422
2
34
Order By: Relevance
“…This positive effect of dam parity on the size of the calf corresponds to other sources (Kertz et al, 1997). On the other hand, maternal metabolic state also affects foetal growth and BW in babies (de Rooij et al, 2006), lambs (Freetly et al, 2000) and calves (Freetly et al, 2000;Micke et al, 2009;Du et al, 2010;Micke et al, 2010). This effect could not be confirmed in the current study.…”
Section: Discussioncontrasting
confidence: 70%
“…This positive effect of dam parity on the size of the calf corresponds to other sources (Kertz et al, 1997). On the other hand, maternal metabolic state also affects foetal growth and BW in babies (de Rooij et al, 2006), lambs (Freetly et al, 2000) and calves (Freetly et al, 2000;Micke et al, 2009;Du et al, 2010;Micke et al, 2010). This effect could not be confirmed in the current study.…”
Section: Discussioncontrasting
confidence: 70%
“…During development perirenal adipose tissue appears at 80 days after conception, followed by subcutaneous and intermuscular adipose tissue at 180 days after conception (Bonnet et al, 2010). Du et al (2010) proposed that the fetal stage offers the greatest chance to improve the ability of livestock to deposit intramuscular fat due to a greater abundance of non-committed pluripotent cells. Studies utilizing sheep have reported adipose tissue in the fetus can be manipulated by maternal nutrition (Bispham et al, 2003;Ford et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Successive groups of myoblast will migrate, align and fuse to form secondary myofibers later in the fetal stage of myogenesis. It is reported that the fetal stage is the only time in development when fiber number can be altered, more specifically between 2 and 8 months of gestation (Russell and Oteruelo, 1981;Du et al, 2010). This period of gestation coincides with secondary myogenesis, and research has determined that secondary fibers are susceptible to maternal nutrient restriction .…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the length and rate of supplementation utilized herein were insufficient to impact the aforementioned variables, despite the long-term increase in hepatic IGF-I and adipose PPARγ mRNA expression that suggests a metabolic imprinting effect (Du et al, 2010). Heifers utilized by Gasser et al (2006) and Moriel et al (2014b) consumed a corn-based diet for, respectively, 10 week at 2.5% to 3.0% of heifer BW or 90 days at 3.5% of heifer BW.…”
mentioning
confidence: 98%
“…Hence, nutritional interventions that improve nutrient utilization, body fat accretion, and increase circulating concentrations of hormones that facilitate the puberty process, such as IGF-I and leptin, are known to hasten puberty attainment in heifers (Williams et al, 2002; Cooke et al, 2008). Metabolic imprinting, defined as biological responses to a nutritional intervention during early life that permanently alters physiological outcomes later in life (Du et al, 2010), has been shown to enhance nutrient metabolism and fat accretion in cattle (Graugnard et al, 2010;Moriel et al, 2014a). Scheffler et al (2014) reported that feeding a highconcentrate diet to early-weaned beef steers from 100 to 205 days of age enhanced carcass marbling compared with forage-fed steers weaned at 205 days of age.…”
mentioning
confidence: 99%